2018
DOI: 10.1103/physrevb.97.024430
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous magnetic and spin glass behavior in Nb-substituted LaCo1xNbxO3

Abstract: We report the structural, magnetic, transport and electronic properties of Nb substituted LaCo1−xNbxO3 (x = 0-0.2). The Rietveld analysis of x-ray diffraction data demonstrate structural phase transitions from rhombohedral to orthorhombic and further to monoclinic with increasing the Nb concentration up to x ≥ 0.2. Interestingly, we observed dramatic changes in the magnetization (M) with increasing the Nb concentration, as the M sharply increases below 10 K even at 2.5% substitution. Furthermore, ac susceptibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 78 publications
7
20
0
Order By: Relevance
“…It is well reported that regardless of having larger ionic radii, Sr 2+ does not induce any structural transformation in the system up to 50% concentration [36]. Whereas, our recent study reveals that the Nb 5+ substitution at Co site induces structural transformation of lower symmetry from the rhombohedral to orthorhombic, and then monoclinic at higher concentration [7].…”
Section: Introductionmentioning
confidence: 50%
See 4 more Smart Citations
“…It is well reported that regardless of having larger ionic radii, Sr 2+ does not induce any structural transformation in the system up to 50% concentration [36]. Whereas, our recent study reveals that the Nb 5+ substitution at Co site induces structural transformation of lower symmetry from the rhombohedral to orthorhombic, and then monoclinic at higher concentration [7].…”
Section: Introductionmentioning
confidence: 50%
“…We used strontium carbonate (SrCO 3 ), cobalt oxide (Co 3 O 4 ) and niobium oxide (Nb 2 O 5 ) as purchased, whereas purchased lanthanum oxide (La 2 O 3 ) powder was dried at 700 0 C for 12 hrs prior to use. Stoichiometric amount of starting materials (all ≥99.9% from Sigma/Alfa) were thoroughly mixed with the help of mortar-pestle and reacted at 1100 0 C for 12 hrs in air, pellets of calcined powder were cold pressed at 2000 psi and sintered in air at 1475 0 C for 6 -10 hrs [7,37].…”
Section: Polycrystalline Samples Of Lamentioning
confidence: 99%
See 3 more Smart Citations